Accurate spectroscopic calculations on low-lying electronic states of ZnI including spin-orbit coupling effect. (May 2020) - Li, Rui; Xu, Linxuan; Teng, Yongfu; Liang, Guiying; Zhao, Shutao; Wu, Yong
Highlights: l The potential energies of 14 Λ-S states of ZnI are computed by MRCI method. l The spin-orbit coupling and 3d 10 correlation effects are included in the calculation. l Spectroscopic constants of bound states of ZnI are evaluated. l The predissociation mechanism of 2 2 Π of ZnI are analyzed. l Radiative lifetimes of 2 2 Π and B 2 Σ + states of ZnI are determined. Abstract: A detail ab initio study on the low-lying states of ZnI is carried out by means of the multireference configuration interaction plus Davidson correction (MRCI+Q) method. The spin-orbit coupling (SOC) effect of the low-lying states is considered by utilizing relativistic effective core potential spin-orbit operator. The potential energy curves (PECs) are provided in the absence of SOC (14 Λ-S states) and presence of SOC (30 Ω states). The spectroscopic constants of bound states are calculated, which are in good agreement with the existing experimental results. With the help of the calculated SOC matrix elements, the predissociation mechanism of 2 2 Π is analyzed. Finally, transition dipole moments, Franck-Condon factors, and the radiative lifetimes of bound states are obtained, which are in accordance with previous measurement. Graphical abstract: Image, graphical abstract